INTERPERSONAL COMMUNICATION BETWEEN PARENTS AND CHILDREN TO FORM CHARACTER FROM AN ISLAMIC PERSPECTIVE - Adinda Sabrina Salsabila; Hana Kamilah; Muhammad Rizki Sya’bani; Sari Nurulita; Rihlah Nur Aulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Interpersonal communication between parents and children is essential for character development. This study investigates the role of Islamic interpersonal communication in the process of character formation in children. A qualitative approach utilizing a literature review method was employed. Data were obtained from journals and previous research and subsequently analyzed. The findings demonstrate that Islamic communication patterns, including qoulan balighan (religious dialogue) and qoulan sadidan (religious dialogue), as well as methods such as two-way discussions and the use of role models, contribute positively to character development in children